1984
DOI: 10.1172/jci111331
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of verapamil intoxication with 4-aminopyridine in the cat.

Abstract: Abstract. To study the value of 4-aminopyridine as an antidote to verapamil intoxication, we subjected 12 adult cats to verapamil poisoning by administering doses of 4.0-25.0 mg/kg verapamil by intravenous infusion. Six animals were given 4-aminopyridine 2 X 0.5 mg/kg i.v. after the verapamil infusion was stopped and the other six animals (the control group) were not. Verapamil caused profound cardiovascular depression and also partial neuromuscular block, both of which were completely reversed by 4-aminopyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…4-Aminopyridine (2 mg/kg) increased blood pressure and heart rate. Moreover, 4-aminopyridine (2×0.5 mg/kg IV) reversed cardiodepression and hypotension completely within 50 min in a cat model of verapamil poisoning [13]. Similarly, 4-aminopyridine (1 mg/kg) produced improvements in heart rate, MAP, and cardiac output in verapamil poisoned dogs [14].…”
Section: Discussionmentioning
confidence: 94%
“…4-Aminopyridine (2 mg/kg) increased blood pressure and heart rate. Moreover, 4-aminopyridine (2×0.5 mg/kg IV) reversed cardiodepression and hypotension completely within 50 min in a cat model of verapamil poisoning [13]. Similarly, 4-aminopyridine (1 mg/kg) produced improvements in heart rate, MAP, and cardiac output in verapamil poisoned dogs [14].…”
Section: Discussionmentioning
confidence: 94%
“…4-AP facilitates calcium conductance by blocking potassium channels on the cytoplasmic side of the cellular membrane, causing depolarization and opening of voltage-gated calcium channels. Rodent and feline models have displayed improvement of hemodynamic outcomes with infusion doses of 2 mg/kg [28][29][30]. The 1 mg/kg dose did produce improvements in verapamil-poisoned dogs but not in other animals [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Rodent and feline models have displayed improvement of hemodynamic outcomes with infusion doses of 2 mg/kg [28][29][30]. The 1 mg/kg dose did produce improvements in verapamil-poisoned dogs but not in other animals [28][29][30][31]. In a rodent model of verapamil poisoning, Graudins and Wong demonstrated that cardiac output and blood pressure improved with 4-AP alone and in combination with levosimendan.…”
Section: Introductionmentioning
confidence: 99%
“…Volume 77, June 1986, 1805-1811 as treatment for verapamil toxicity (7). To systematically evaluate the effectiveness of different pharmacologic agents in the treatment of verapamil intoxication, lightly sedated dogs were given large doses of intravenous verapamil and then the responses to calcium, isoproterenol, atropine, dopamine, epinephrine, norepinephrine, phenylephrine, and 4-AP were measured.…”
Section: Introductionmentioning
confidence: 99%